KEANEKARAGAMAN JENIS INVERTEBRATA YANG BERASOSIASI DENGAN EKOSISTEM TERUMBU KARANG DI PERAIRAN TELUK PALU KELURAHAN PANAU KOTA PALU - Gani, Abdul; Rosyida, Eka; Serdiati, Novalina (AgriSains, 2017)
Marine invertebrates are animals that have no vertebrae and are almost found throughout marine areas, including coastal areas such as coral reefs. The study aims to determine the diversity of invertebrate species associated with coral reefs in the waters of Palu Bay, Panau Village, Palu. The number of invertebrates found in coral reefs were 558 individuals in the day (22 families), while at night as many as 670 individuals (24 families). Family Pectinidae has the highest abundance, both in the day (50.17%) and night (41.79%) with the number of 280 individuals. The value of diversity index during the day ranged from 1.03 to 1.67, while at night the diversity index ranged from 1.72 to 1.81 and categorized as low. The homogeneity index during the day for all transects ranged from 0.27 to 0.40, while at night ranged from 0.31 to 0.34 categorized as the community under stress. The dominance index during day and night for all transects are categorized as low, which for daytime ranges from 0.21 to 0.39, whereas the night ranges from 0.24 to 0.28.